2018
DOI: 10.1159/000489074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Concanavalin a-Induced Murine Autoimmune Hepatitis Models

Abstract: Background/Aims: Autoimmune hepatitis (AIH) is a chronic necroinflammatory disease of the liver whose pathogenic mechanisms have not yet been elucidated. Moreover, the current treatment used for the vast majority of AIH patients is largely dependent on immunosuppressant administration and liver transplantation. However, research on the pathogenesis of AIH and effective new treatments for AIH have been hampered by a lack of animal models that accurately reproduce the human condition. Methods: AIH models created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…The EAH model was established at 12 h after an injection of ConA with a dose of 20 mg/kg through the tail vein, which was based on our previous study and other reported articles [11][12][13][14] . To evaluate the EAH model, the mice were divided into two groups: (1) Mice were given a single intravenous injection of normal saline as a vehicle control.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAH model was established at 12 h after an injection of ConA with a dose of 20 mg/kg through the tail vein, which was based on our previous study and other reported articles [11][12][13][14] . To evaluate the EAH model, the mice were divided into two groups: (1) Mice were given a single intravenous injection of normal saline as a vehicle control.…”
Section: Experimental Designmentioning
confidence: 99%
“…To investigate the role of cDCs in the pathogenesis of EAH, we developed a mouse model of ConA-induced AIH as in our previous study 11,14,19 . As shown by liver function and H&E, EAH was successfully established after ConA injection in EAH model ( Supplementary Fig.…”
Section: Circulating and Intrahepatic Mature Cdc Accumulation In Eahmentioning
confidence: 99%
“…Nonetheless, even though it is inconsistent with the potent anti-inflammatory action of IL37 in experimental studies, the hypothesis can neither be ruled out that the augmented levels of IL37 may play an unexpected pathogenetic role in these autoimmune diseases by activating unknown inflammatory pathways that have so far not been recognized to be modulated by IL37. Cytokines exerting primarily anti-inflammatory effects have subsequently been shown to be also capable of upregulating immunoinflammatory responses, as has been shown with endogenous IL4 in models of autoimmune hepatitis [29] and exogenously administered IL10 in models of orchitis [30]. Vice versa, anti-inflammatory effects of prototypical Th1 cytokines such as IFN-γ and also TNF-α have been reported in models of type 1 diabetes [31,32].…”
Section: Introductionmentioning
confidence: 94%
“…model to study this disease [3]. Concanavalin A (ConA) may induce a typical T cell-mediated hepatitis in mice characterized by immune cell infiltration and severe liver damage [4]. Many studies related to the pathophysiology of immunologically mediated hepatic disorders such as autoimmune chronic active hepatitis were based on this mouse model [5][6][7].…”
mentioning
confidence: 99%
“…Over the past decades, several researchers have tried to establish appropriate animal models, but a widely accepted AIH mouse model has not yet been recognized [4,9,10]. AIH is divided into two main types based on the serological autoantibody profile: type-1 AIH and type-2 AIH [2].…”
mentioning
confidence: 99%